1990
DOI: 10.1111/j.1365-3016.1990.tb00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Health, growth and sexual development of teenagers exposed in utero to medroxyprogesterone acetate

Abstract: General health, growth and sexual development were evaluated in 74 teenage boys and 98 girls who had been exposed to medroxyprogesterone acetate (MPA) in utero, and 385 boys and 448 girls not exposed. In this 17-year prospective study, the ascertainment of the end points was 'double blind' in that neither the interviewer nor the subject was aware of our interest in MPA. On average, girls exposed to MPA reported reaching the menarche 4 months earlier than the comparison group. This difference disappeared, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In recent studies, we found this scale to predict subsequent schizophrenia in offspring 19 and long‐term mortality in mothers 20 . Earlier work had suggested effects of social class on specific complications of pregnancy and labour, 21 and our scale was used as a covariate in studies of birthweight, 22–24 adolescent maturation 15 and cognitive ability 13 . Other studies used the municipal tax level of the census tract as an indicator of socio‐economic status 25 …”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…In recent studies, we found this scale to predict subsequent schizophrenia in offspring 19 and long‐term mortality in mothers 20 . Earlier work had suggested effects of social class on specific complications of pregnancy and labour, 21 and our scale was used as a covariate in studies of birthweight, 22–24 adolescent maturation 15 and cognitive ability 13 . Other studies used the municipal tax level of the census tract as an indicator of socio‐economic status 25 …”
Section: Resultsmentioning
confidence: 79%
“…A few minor differences were found comparing MPA‐exposed and non‐exposed offspring, most being due to the more favourable distribution of social variables in the exposed group. The study provided data on the prevalence of various health conditions in teenagers, on factors associated with puberty, and on gender‐dimorphic measures of cognitive ability, aggression and behaviour in school 13–15,76 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred and seventy two children, who were exposed in utero to oral MPA or DMPA (analysed together), were followed up for 17 years. These adolescents exhibited no evidence of adverse effects on their general health or on their physical, intellectual or sexual development 39 .…”
Section: Side Effectsmentioning
confidence: 89%
“…For other oestrogen and progestin drugs, some studies show a positive relation to genital malformations, others not (Heinonen et al, 1977;Goldstein et al, 1989;Briggs et al, 1994). In a follow-up study, sons exposed prenatally in utero to medroxyprogesterone had undescended testicles and inguinal hernia more frequently than control sons, but the difference was not statistically significant (Jaffe et al, 1990). Prenatal exposure to oestrogen has been reported to be a risk factor for testicular cancer, cryptorchidism and hypofunctional testes (Depue et al, 1983), and germ-cell tumours of testes and ovaries (Preston-Martin, 1989); there are no previous studies on other cancers of the daughter or any cancer of the mother.…”
mentioning
confidence: 99%